THE CORELATION OF THE QUALITY OF ANTENATAL CARE VISITS WITH THE INCIDENT OF ASPHYXIA NEONATORUM AT PHC HOSPITAL SURABAYA - Noorlaksmiatmo, Harno Prihadi; Budipramana, Edwin; Tahalele, Paul L; Merici, Angela (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Birth asphyxia is the one of the very common problem in neonatal health care. Its incidence is very high in the developing country where health facilities are restricted to urban area, and these factors can be prevented through standard Antenatal Care (ANC) visits. ANC is medical care provided by healthcare professionals to mothers during pregnancy, administered by medical personnel and conducted according to established standards. This ANC monitors the health and development of both the mother and the fetus for early detection of risks and health issues during pregnancy.Objective: To determine the relationship between the quality of ANC visits and the occurrence of Asphyxia Neonatorum at PHC Hospital Surabaya.Method: This research is an observational analytic study with a case-control study design, employing a retrospective approach. The sampling in the study utilized probability sampling, specifically employing the simple random sampling technique. The statistical method used to examine the relationship between the quality of ANC visits and Asphyxia (APGAR Score ≤3-6) through the analysis of odds ratio comparison using the Chi-square statistical test.Result: The statistical analysis of the relationship between the quality of ANC visits and the occurrence of Asphyxia shows significant results with a p-value of 0.001 (p < 0.05).Conclusion: The compliance of pregnant women in adhering to standard ANC visits ensures the health of both the mother and the baby during pregnancy.